Reading in the first study: “the person and the assigned identifier is a semantic approach” “Paul Ricoeur’s” book: “the self is the same as the other” - Djamila Rahabi (Social Empowerment Journal, 2020)
Tried to Paul Ricoeur be exposed to meaning initial of what person as transefer specific identity, eagerness to statement interpretations fundamental given to identity, have begun from the description person like something of things that talk about them as subjective naming, the person could not be considered just consciousness pure add to it body secondary. But relationship ego in the world are not directly but meduim- term each other and symbol and language, the identity of the person them double can bejudged identity persistent recurrent from the direction, in the second place identity individual free interactive with others and continuous to them.